2021
DOI: 10.1177/08862605211006359
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Short-term Changes in Relationship Conflict During COVID-19: A Risk and Resilience Perspective

Abstract: This study uses a risk and resilience framework to examine short-term self-reported changes in relationship conflict early in the COVID-19 pandemic (March and April 2020). Longitudinal data from U.S. adults in a romantic relationship ( N = 291) were collected via three waves of an online survey. Participants self-reported anxiety, depression, increased alcohol use, and dyadic coping since the pandemic. Relationship conflict variables included whether the participant reported that they and their partner “had di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 47 publications
3
44
1
2
Order By: Relevance
“…길어지면서 아동 및 배우자 혹은 파트너에 대한 폭력, 가 족 간 갈등이 증가하고 있음이 보고되고 있다 [17][18][19]. 또 한 COVID-19 동안 사람들은 평소보다 더 많은 의견 차 이와 말다툼을 경험한 것으로 보고되며 [20], 사회적 접촉 이 감소한 상태에서 육아와 일의 균형이 맞지 않고, 스트 레스가 증가함에 따라 결혼 생활 갈등과 가정폭력이 증가 하였으며, COVID-19로 인한 부정적 영향을 크게 느끼는 부모일수록 양육 스트레스가 높았고, 이는 부정적인 양육 행동으로 이어졌다 [21]. 더욱이 실직이나 임금감소를 경 험하는 경우 이러한 스트레스는 더욱 높아져 저소득층이 나 대가족에서 이러한 어려움이 더욱 커졌다 [20,21].…”
unclassified
“…길어지면서 아동 및 배우자 혹은 파트너에 대한 폭력, 가 족 간 갈등이 증가하고 있음이 보고되고 있다 [17][18][19]. 또 한 COVID-19 동안 사람들은 평소보다 더 많은 의견 차 이와 말다툼을 경험한 것으로 보고되며 [20], 사회적 접촉 이 감소한 상태에서 육아와 일의 균형이 맞지 않고, 스트 레스가 증가함에 따라 결혼 생활 갈등과 가정폭력이 증가 하였으며, COVID-19로 인한 부정적 영향을 크게 느끼는 부모일수록 양육 스트레스가 높았고, 이는 부정적인 양육 행동으로 이어졌다 [21]. 더욱이 실직이나 임금감소를 경 험하는 경우 이러한 스트레스는 더욱 높아져 저소득층이 나 대가족에서 이러한 어려움이 더욱 커졌다 [20,21].…”
unclassified
“…During two months of quarantine, roles and responsibilities, shared things, routines of couples underwent a change and many people found themselves in search of looking for the elements balancing the family and work lives. In such a kind of a transition process, especially, it is inescapable for couples to experience conflict at times (Mazza et al, 2020), changes in communication style and behavioral differences for each other. Changes in relationships brought about by quarantine and reflections of individual mental health to marital relationships are expected outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic period, in marriages, economical concerns of one or two of the spouses, losing jobs, economic hardship, challenge of maintaining their job from home during quarantine period, parental stress caused by education and care of children, changes in relationship with close environment, problems related to health condition of family, the fear that one of the family members will be infected, and ambiguities of pandemic period create critical relationship difficulties on marital relationships (e.g., Daks et al, 2020;Lee et al, 2020a, b;Lian & Yoon, 2020;Pietromonaco & Overall, 2021). Furthermore quarantine may increase contact between partners and exacerbate a potential conflict (Mazza et al, 2020). In addition, when it is thought that marriages are affected by the situations they are exposed to, it is expected that spouses give varied reactions.…”
Section: Dyadic Coping To Relational Resilience In Marriage Relationshipmentioning
confidence: 99%
“…Among those who were currently in a relationship, the majority said they had reduced or stopped spending time together in person. One responded, "I haven't seen my boyfriend and when I have I had to wear a mask" (female, straight, age 16).…”
Section: Physical Distancing From Intimate Partners During the Covid-19 Pandemicmentioning
confidence: 99%
“…Researchers have posited that social distancing and stay-at-home guidelines have resulted in less partnered sex for most young people as they face increased parental monitoring and reduced privacy [10]. Studies in adult populations have found evidence of significant declines in sexual activity during the pandemic, although adults did not completely stop engaging in sexual activities [11][12][13][14], as well as evidence of increased romantic relationship conflict [15,16]. Comparatively few studies in this area have included adolescent or young adult populations.…”
Section: Introductionmentioning
confidence: 99%